Avaliação da via inibitória do sinal insulínico em ratos adultos, proles de ratas com doença periodontal - Shirakashi, Daisy Jaqueline [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Fetal environment has been pointed out as being a possible causal factor of diabetes mellitus, because there is a phenomenon known as programming, which suggests that any stimulation or aggression during a critical period of intrauterine life results in physiological and metabolic alterations in adulthood. Studies have reported that both periodontal disease (PD) and increase in adipose tissue raise the cytokine plasma level. Cytokines such as TNF-α can cause alteration in insulin signaling. Previous studies from the authors' laboratory have demonstrated that offspring of rats with periodontal disease showed insulin resistance and decrease in tyrosine phosphorylation status in periepididymal white adipose tissue and gastrocnemius skeletal muscle. To investigate which mechanisms are involved in these alterations, the aim of present study was to evaluate: 1) IRS-1 serine phosphorylation status after insulin stimulation in gastrocnemius skeletal muscle (GM), periepididymal white adipose tissue (WAT) and liver (L); 2) quantification of IRβ and IRS-1 content in GM, WAT and L; 3) cholesterolemia and triacylglyceridemia; 4) TNF-α, IL-6, resistin and adiponectin plasma concentrations; 5) fructosaminemia; 6) amylasaemia and lipasaemia. Male and female rats (2-month-old) were used. Female rats were divided into two groups: 1) periodontal disease group (PD) - with periodontitis induced by silk thread placed in cervical region of mandibular first molars; 2) control group (CN). Seven days after ligature placement, animals from both groups mated and daily vaginal smears were taken to verify the presence of sperm. Pregnant rats were kept in individual cages. After birth, the numbers of offspring from CN and PD mothers were paired and they were divided into: control offspring...

O ambiente fetal tem sido apontado como possível fator causal de diabetes mellitus, pois há um fenômeno conhecido como programming, sugerindo que um estímulo ou agressão durante um período crítico da vida intra-uterina resulta em alterações na fisiologia e no metabolismo, na vida adulta. Estudos demonstraram que tanto a doença periodontal (DP) como o aumento do tecido adiposo elevam o nível de citocinas plasmáticas. Ademais, citocinas, como por exemplo, o TNF-, podem ocasionar alteração no sinal insulínico. Estudos anteriores do nosso laboratório demonstraram que proles de ratas com doença periodontal apresentaram resistência à insulina e diminuição no grau de fosforilação em tirosina no tecido adiposo branco periepididimal e muscular esquelético gastrocnêmio. Para averiguar quais mecanismos estão envolvidos nestas alterações, o objetivo do presente estudo foi avaliar: 1) o grau de fosforilação em serina do IRS-1, após o estímulo insulínico, em músculo esquelético gastrocnêmio (MG), tecido adiposo branco periepididimal (TAB) e fígado (F); 2) quantificação dos conteúdos de IRβ e de IRS-1 em MG, TAB e F; 3) colesterolemia e triacilgliceridemia; 4) concentração plasmática de TNF-α, IL-6, resistina e adiponectina; 5) frutosaminemia, 6) amilasemia e lipasemia. Para tanto, foram utilizados ratos e ratas Wistar (2 meses de idade). As ratas foram divididas em dois grupos: 1) grupo com doença periodontal (DP) induzida por meio da ligadura com fio de seda ao redor do 1º molar inferior; 2) grupo-controle (CN). Após 7 dias da colocação da ligadura, as ratas de ambos os grupos foram colocadas para acasalamento, verificando-se diariamente, por esfregaço vaginal, o dia da copulação. As ratas prenhas foram separadas em caixas individuais e, após o nascimento, os filhotes foram...
Keywords: Doenças periodontais; Citocinas; Diabetes mellitus; Resistência à insulina; Inflamação; Periodontal diseases